The role of rehabilitation in patients with pulmonary arterial hypertension - Eichstaedt, Christina; Benjamin, Nicola; Xanthouli, Panagiota; Marra, Alberto M.; Grünig, Ekkehard (Current opinion in pulmonary medicine, 2019)
Purpose of review The current review summarizes the latest evidence of the effects of exercise training for pulmonary hypertension patients demonstrated by six randomized controlled trails and 20 further studies. As the availability of exercise training is still limited it is important to raise awareness of the body of evidence showing the benefit for the patients and the limitations. Recent findings The effects of exercise training on exercise capacity, hemodynamics as well as quality of life are described as well as different settings and components of exercise training. Associated adverse events are critically reviewed and strategies for avoidance of these events discussed. Lastly, the most important issues of availability and reimbursement of a specialized exercise training program are examined and the future path is outlined to improve patient access. The latest publications on this topic strengthen the call for international multicenter randomized controlled trials to establish the feasibility of exercise training in different healthcare systems and to enhance patient access to these programs.
Gesehen am 29.01.2020